Social media in the public sector: comparative analysis of the adoption of Facebook in two Municipalities of Mexico City - Ramos Alderete, José Luis (Estado, Gobierno y Gestión Pública, 2024)
In the public sector, the use of social media has become widespread. The Open Government views them as a means with great potential to put its proposals into practice. Different investigations show that local governments tend to use social media in a limited way in relation to their potential to generate conversation with citizens, take into account what they express and address their demands. The objective of this research is to make a comparative analysis of the adoption of Facebook in two municipalities of Mexico City in order to offer concrete measurements on three dimensions of its interaction with citizens: 1) relationship/interaction 2) communication and 3) management/attention. The data analyzed allows us to notice that the use of social media is at a communication level with slow progress towards more interactive levels that promote citizen participation and better management of services.